“Integrating Flipped Classroom and Multimedia Tools to Improve Fine Arts Education in Higher Institutions” - Kodirov Obid Esonboy o‘g‘li (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the integration of flipped classroom methodology with multimedia tools to enhance fine arts education in higher education. The study analyzes how combining pre-class learning, interactive digital resources, and in-class collaborative activities can improve students’ artistic perception, creative thinking, and aesthetic literacy. Pedagogical strategies are discussed for effectively implementing this integrated approach to increase student engagement, foster independent learning, and support the development of critical analysis and practical skills in fine arts.